(خلال العهد العلوي (1664/1830)العلاقات الثقافية بين الجزائر و المغرب الأقصى - أمينة بوشرمة; كوثر بن تريعة (My University, 2023)
abstract The cultural relationship between Morocco and Algeria was generated as a result Algeria’s recession its scientists sought refuge in migration towards Morocco to develop their knowledge and gain a new scientific experiences, meanwhile morocco’s political and cultural situations had developed and got better as a result of the Alawi’s takeover the government, which they developed education and took care of buildings construction, thus the divers trips among the scientists of the two countries contributed in strengthening spiritual and cultural connection. the vacations had an important role to keep the connection between scientists, with the appearance of Sufi orders and it’s principles and it’s widespread helped to connect the two countries due to their religious, ideological and linguistically closeness, through its transition between the two countries. ------------------------------------------------------------------ ملخص الدراسة باللغة العربية تولدت العلاقات الثقافية بين الجزائر والمغرب الأقصى نتيجة للركود الذي كانت تعيشه الجزائر فقد لجأ علمائها إلى الهجرة نحو المغرب الأقصى لتطوير معارفهم واكتساب خبرات علمية جديدة، في حين أن المغرب كانت أوضاعها السياسية والثقافية قد تطورت وتحسنت نتيجة لاستيلاء العلويين على الحكم والذين طوروا التعليم واهتموا بتشييد المباني، حيث ساهمت الرحلات المتنوعة بين علماء البلدين في تقوية الصلات الروحية والثقافية. وكذلك الإجازات بين علماء البلدين كان لها دور هام في المحافظة على هذه الصلات، ومع ظهور الطرق الصوفية بمبادئها وانتشارها على نطاق واسع قد ساعدت على ربط البلدين نظرا لتقاربهم الديني والعقائدي واللغوي من خلال انتقالها بين البلدين ---------------------------------------------------- résumé Les relations culturelles entre l'Algérie et Al-Maghreb Al-Aqsa ont été générées à la suite de la stagnation que connaissait l'Algérie. Les différents voyages entre les savants des deux pays ont contribué à renforcer les liens spirituels et culturels. De même que les vacances entre les savants des deux pays ont joué un rôle important de maintenir ces liens, et avec l'émergence des ordres soufis avec leurs principes et leur large diffusion, ils ont contribué à lier les deux pays du fait de leur rapprochement religieux, idéologique et linguistique à travers leur transmission entre les deux pays.